Generalized random processes and Cauchy's problem for some partial differential systems - Mahmoud M. El-Borai (International Journal of Mathematics and Mathematical Sciences)
In this paper we consider a parabolic partial differential system of the form DtHt=L(t,x,D)Ht. The generalized stochastic solutions Ht, corresponding to the generalized stochastic initial conditions H0 are given. Some properties concerning these generalized stochastic solutions are also obtained.